Disaster Management Policy Analysis At the Regional Disaster Management Agency BPBD Palu City - Nur Aisyah; Dandan Haryono; M.Syukur M.Syukur (CV. Publikasi Indonesia, 2023)
Palu City is one of the regions in Indonesia with a level of vulnerability to various natural disasters. One of the policies that regulate disaster management is Law No. 24 of 2007 concerning disaster management, and Palu city regional regulation No. 5 of 2011 concerning the implementation of disaster management. The implementation of disaster management is a crucial stage in the public policy process. The implementation of disasters in the city of Palu is carried out by BPBD which was formed based on regional regulations. BPBD is a supporting element of the duties of the Regent / Mayor in the administration of local government in the field of disaster management, led by a head of the agency under the responsibility of the regent / mayor. The method used in this study is qualitative with a descriptive approach, where the data source comes from primary data (direct interviews with informants) and secondary data from the results of review documents related to disaster management. From the results of the analysis of disaster management policies in Bandan Regional Disaster Management BPBD Palu city has not been implemented effectively. This is because of the four indicators used as measuring instruments, namely communication, resources, disposition, and bureaucratic structure, there are only two indicators that have been implemented well, namely disposition and communication. While the other two indicators have not been implemented properly